KARAŞAR, AN ALEVI-BEKTASHI SETTLEMENT IN BEYPAZARI (ADMINISTRATIVE, ECONOMIC AND SOCIAL STRUCTURE) - İsmail Yaşayanlar (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi)
Karaşar is an example of the settlement of Alevi-Bektashi Turkmen groups in Anatolia during the early Ottoman period, and the earliest records of Karaşar date to the 15th century. In the Ottoman period, Karaşar was administratively located at the intersection of the borders of the provinces of Hudavendigar, Kastamonu and Ankara, and historically always remained a part of Beypazarı. Karaşar, which had a considerably higher population compared to a classical village settlement, became a subdistrict to which other villages around it were connected in the 19th century. In the Republican period, Karaşar became a town, and although it maintained this status for many years, today it is a settlement consisting of several neighborhoods. This study evaluates the economic and social structure of Karaşar, an Alevi-Bektashi settlement, on the basis of data from tahrir, population and temettuat books in the Ottoman Archives. In addition, the smuggling and banditry issues that have taken place in the history of Karaşar have been emphasized. The evaluations based on archives and research works are also supported by oral history data in Karaşar. The oral history data has been especially important in terms of the continuity of intangible cultural heritage and the control of local narratives with historical data.